Parteien, Politik und Staatsgewalt in Dalmatien (1900-1918) Zur Wechselwirkung zwischen staatlicher Verwaltung und parlamentarischer Vertretung - Kalwoda, Johannes (Verlag der Österreichischen Akademie der Wissenschaften, 2023)
Exemplary deep drilling of political events in Dalmatia (1900-1918) forms the basis of this profound study investigating the actions of the Austrian state administration. The elections of the Imperial Council and the Dalmatian Diet, the Bosnian annexation crisis in 1908/09, the "Sprachenausgleich" of 1909, the political development before/during WW I, the dissolution of the municipal councils (1914-18) and the attitude of the Dalmatian Reichsrat members during WW I are all focused on in this analysis.